Expression of vitamin D receptor in naevi and melanoma. (1st July 2018) - del Puerto, C.; Navarrete‐Dechent, C.; Molgó, M.; Camargo, C.A.; Borzutzky, A.; González, S.
Summary: Deficiency of vitamin D is associated with an increased risk of cancer. Although its importance in malignant melanoma is debated, vitamin D does appear to suppress the growth of the non‐melanoma skin tumours basal cell carcinoma and squamous cell carcinoma. This study from Santiago, Chile, and Boston, USA, looked at whether the vitamin D receptor in melanoma cells was lost in comparison with mole cells. Both are formed from cells called melanocytes; the difference is that the melanocytes are malignant in melanoma, benign in moles. Melanoma samples were taken from 54 patients and compared with 55 samples of moles from patients with no history of melanoma or abnormal ("dysplastic") moles. The melanoma samples were looked at down the microscope and classified according to standard measures such as thickness, depth of invasion into the skin, ulceration, etc . They were specially stained to show up the vitamin D receptor. The intensity of staining, and the numbers of cells that showed vitamin D receptor in both the nucleus and cytoplasm, were assessed. There was significant loss of the vitamin D receptor in the cytoplasm, though not the nucleus, of melanoma cells in comparison to mole cells. This was associated with the thickness and staging of the melanoma in the skin: the thicker the tumour, the more vitamin D receptor was lost. Similar findings have been reported in carcinomas of the prostate, stomach and pancreas. The degree of loss of vitamin D receptor may help decide which patients might benefit from taking vitamin D.